2022
DOI: 10.7150/thno.75965
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive therapy with amyloid-β specific regulatory T cells alleviates Alzheimer's disease

Abstract: Rationale:Neuroinflammation is a primary feature of Alzheimer's disease (AD), for which an increasing number of drugs have been specifically developed. The present study aimed to define the therapeutic impact of a specific subpopulation of T cells that can suppress excessive inflammation in various immune and inflammatory disorders, namely, CD4 + CD25 + Foxp3 + regulatory T cells (Tregs). Methods: To generate Aβ antigen-specific Tregs (Aβ + Tregs), Aβ 1-42 peptide was applied in vivo and subsequent in vitro sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…In our recently published data, we attempted depletion of adoptively transferred Tregs using the diphtheria toxin in DEpletion of REGulatory T cells (DEREG) mice, and found that adoptively transferred Tregs must survive for more than 7 days to induce neuroprotective effects [24]. In the current study, we tracked adoptively transferred Tregs in several tissues.…”
Section: Discussionmentioning
confidence: 91%
“…In our recently published data, we attempted depletion of adoptively transferred Tregs using the diphtheria toxin in DEpletion of REGulatory T cells (DEREG) mice, and found that adoptively transferred Tregs must survive for more than 7 days to induce neuroprotective effects [24]. In the current study, we tracked adoptively transferred Tregs in several tissues.…”
Section: Discussionmentioning
confidence: 91%
“…The results have, however, been inconsistent across models and with different modalities of treatment. For example, in AD, direct cell therapy with Tregs (Baek et al , 2016 ; Faridar et al , 2022 ; Yang et al , 2022 ) has given beneficial effects, although other studies have shown the reverse (Baruch et al , 2015 ; Yang et al , 2020 ), while treatment with IL2 has given conflicting results, depending on the AD model, ranging from protective (Baek et al , 2016 ; Alves et al , 2017 ) to minor (Dansokho et al , 2016 ) or no effect (preprint: Yshii et al , 2022a ). In PD models, a number of different Treg‐based treatments have been beneficial, including direct cell transfer (Reynolds et al , 2007 ; Huang et al , 2020 ; Markovic et al , 2022 ), using bee venom phospholipase A2 to induce Treg formation, superagonist anti‐CD28 antibodies to expand them (Badr et al , 2022 ) or vasoactive intestinal peptide receptor‐2 (VIPR2) peptide agonist to enhance activity (Mosley et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described above Tregs can play an important immune-modulatory role that contributes to AD pathology. Recent studies have suggested that Tregs can potentially be neuroprotective and can suppress excessive microglia activation and inflammation seen in AD brains [ 156 , 157 ]. These studies took an approach that examines what impact the adoptive transfer of in vitro expanded Tregs has on AD pathology using AD mice.…”
Section: Introductionmentioning
confidence: 99%
“…These studies took an approach that examines what impact the adoptive transfer of in vitro expanded Tregs has on AD pathology using AD mice. Tregs were either isolated from mouse splenocyte cultures and expanded using Aβ1-42 peptide to ensure antigen-specific Tregs were expanded [ 157 ], or were derived from human PBMC cultures and expanded for 24 days [ 156 ]. Expanded mouse Tregs were transferred into 3xTG AD mice where a noted reduction in microglial activation was seen with an associated amelioration of cognitive impairment [ 157 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation